(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: The presence of abnormal monoclonal proteins, the M band, is a frequent characteristic feature of plasma cell dyscrasias and is usually detected as a discrete band in the γ or β region in serum or urine protein electrophoresis. It is characterized and confirmed by immunofixation electrophoresis (IFE). Accurate detection and quantification of monoclonal immunoglobulins are important for the diagnosis and management of monoclonal gammopathies. Objectives: To find out the pattern of immunoglobulin in monoclonal gammopathy cases and evaluate the role of IFE in the detection of them. Materials and Methods: This cross-sectional descriptive study was conducted in the Department of Haematology, Armed Forces Institute of Pathology (AFIP), Dhaka from July 2015 to December 2015. Thirty diagnosed cases of monoclonal gammopathies of both sexes were selected. Bone marrow examination, serum protein electrophoresis, skeletal survey, relevant biochemical test and IFE were performed for all the cases. Results: Out of 30 monoclonal gammopathy cases, M band was identified in 24(80%) cases by serum protein electrophoresis but by the IFE M band was found in all 30(100%) cases. Among the M band pattern of immunoglobulin was characterized by IFE and the result was; 15(50%) cases IgG Kappa, 09(30%) cases IgG Lambda, 02(6.7%) cases IgA Kappa, 02(6.7%) cases IgM Kappa and 02(6.7%) cases light chain kappa monoclonal protein. Conclusion: Though the number of the patient was limited, it is evident that in 20% gammopathy cases M band was missing by conventional serum protein electrophoresis but IFE could identify M band in all the cases. It is recommended that IFE should be carried out in all monoclonal gammopathy patients. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 160-163